The Practice of Training of Local Administration in Opolskie Voivodship — the Research Findings - Tracz-Krupa, Katarzyna (Regional Barometer. Analyses & Prognoses, 2012)
The article deals with the issue of training the local administration in the Opolskie Voivodship. The main goal of the paper was to diagnose and evaluate training of self- administration officials and to indicate possible ways of improvements. The empirical part was conducted amongst 451 officials at different levels of self-administration in the Opolskie Voivodship.